Pengaruh Tipe Penjual di Shopee Terhadap Keputusan Pembelian - Zahra Nur Azizah (International Journal Administration, Business & Organization, 2023)
This study aims to investigate the influence of seller types on the Shopee e-commerce platform on consumer purchasing decisions. This research was conducted by collecting data through an online survey of a few respondents who actively shop at Shopee. Regression analysis was used to identify the relationship between the independent variable, seller type, and the dependent variable, consumer purchasing decisions. The results of this study are expected to provide a deeper understanding of consumer preferences regarding seller types in Shopee and provide valuable insights for sellers to improve their marketing strategies. The practical implications of the findings can support the future development of e-commerce businesses and online marketing.